2016
DOI: 10.1371/journal.pone.0157566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Extracellular Vesicles from the Urine of Healthy Individuals and Prostate Cancer Patients

Abstract: Recent studies suggest that extracellular vesicles may be the key to timely diagnosis and monitoring of genito-urological malignancies. In this study we investigated the composition and content of extracellular vesicles found in the urine of healthy donors and prostate cancer patients. Urine of 14 PCa patients and 20 healthy volunteers was clarified by low-speed centrifugation and total extracellular vesicles fraction was obtain by high-speed centrifugation. The exosome-enriched fraction was obtained by filtra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(145 citation statements)
references
References 59 publications
(81 reference statements)
10
127
1
7
Order By: Relevance
“…Profiles of miRNAs within serum EVs from ovarian cancer patients are significantly different than those of normal patients and of patients with benign cancer [30]. Urinary EVs may be a valuable source of diagnostically-useful miRNAs in prostate cancer [31]. Proteins in urinary EVs may provide biomarkers of acute kidney injury; for example, fetuitin-A in urinary EVs may be useful in diagnosing structural renal injury [32,33], and decrease in the level of podocalyxinlike protein 1 (PODXL) in urinary EVs may provide a biomarker to classify renal disease [34].…”
Section: Open Accessmentioning
confidence: 96%
See 1 more Smart Citation
“…Profiles of miRNAs within serum EVs from ovarian cancer patients are significantly different than those of normal patients and of patients with benign cancer [30]. Urinary EVs may be a valuable source of diagnostically-useful miRNAs in prostate cancer [31]. Proteins in urinary EVs may provide biomarkers of acute kidney injury; for example, fetuitin-A in urinary EVs may be useful in diagnosing structural renal injury [32,33], and decrease in the level of podocalyxinlike protein 1 (PODXL) in urinary EVs may provide a biomarker to classify renal disease [34].…”
Section: Open Accessmentioning
confidence: 96%
“…Two prostate cancer biomarkers, PCA3 and TMPRSS2-ERG, have been detected in urinary EVs from prostate cancer patients [53]. Also, urinary EVs are enriched with miRNAs, so isolation and analysis of urinary EVs can help to identify miRNA biomarkers for diseases such as prostate cancer [31]. Results can provide a diagnostic standard for comparison of patients with healthy individuals [54].…”
Section: Ultracentrifugationmentioning
confidence: 99%
“…Exosomal lincRNA and miRNA are also detected in the urine of prostate and bladder cancer patients [77][78][79]. Bryzgunova et al [77] reported that the level of miR-19b, normalized to that of miR-16, in urine-derived exosomes was significantly lower in prostate cancer patients than in healthy donors .…”
Section: Diagnosismentioning
confidence: 99%
“…Bryzgunova et al [77] reported that the level of miR-19b, normalized to that of miR-16, in urine-derived exosomes was significantly lower in prostate cancer patients than in healthy donors . Armstrong et al also reported that in bladder cancer, high levels of miR-21 and miR-4454 are commonly detected in whole blood cell, tumor, and urine.…”
Section: Diagnosismentioning
confidence: 99%
“…Indeed, the protein and miRNA composition of tumor-derived EVs found in urine have been observed to reflect the presence of cancer [43]. For example, differential protein and miRNA profiles were observed in patients with prostate cancer [105,106]. From 24 proteins known to be differentially expressed in bladder cancer patients, one (TACSTD2) was found to also be present at significantly elevated levels in EVs isolated from urine [107].…”
Section: Extracellular Vesicles (Ev) Isolationmentioning
confidence: 99%